A comparative study of pain following endodontic treatment under general anesthesia - Feizi Ghader; Kaviani Naser; Mehrparvar Roza; Binandeh Elham Sadaat; Tabrizizadeh Mehdi; Saatchi Masoud (Tehran University of Medical Sciences, 2015)
Background and Aims: Postoperativee endodontic pain is an outstanding problem for dental patients. Therefore, a successful management of endodontic pain has become as one of the main dental objectives. The aim of the present study was to compare the postoperative endodontic pain in patients under general anesthesia versus local anesthesia.   Materials and Methods: For conducting this clinical trial study, 50 patients having mandibular molars candidate for root canal therapy were selected. Twenty-five patients treated under general anesthesia because of their fear, anxiety or gag reflex. Other 25 patients treated under local anesthesia. All teeth were prepared using engine-driven rotary system in a crown-down technique and filled using lateral condensation technique. Heft- parker visual analog scale was used to measure the degree of pain at 6, 12, 24, and 48 hours after the treatment. Mann-Whitney, Chi-square, and T-tests were used to compare the intensity of postoperative pain between the groups.   Results: The mean intensity of postoperative pain in local and general anesthesia groups at 6, 12 and 24 hours had statistically significant difference (P<0.05).   Conclusion: Postoperative pain in patients who treated under general anesthesia was significantly less than the patients who treated under local anesthesia.